(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Accounting frameworks for accounting accounting have an impact on the efficiency of investment in public companies listed on the Iraqi Stock Exchange. The aim of this study is to determine the impact of the accounting reservation in the development of investment efficiency, which helps guide investment in large, medium and small companies. The hypothesis (there is no significant relationship between the accounting reservation and the efficiency of investments. And tested the hypothesis in a number of Iraqi private banks listed in the Iraqi market for securities, and using the appropriate statistical methods of analysis, the research ended to a set of conclusions and recommendations to the absence of a relationship of significant effect between models used,To Conduct similar research in other sectors (eg health, public services, agriculture, and financial investment companies),due the different financial statement items for these sectors.. Also increase the size of the sample by taking a larger annual series and documenting them to increase the ability of the models to show the relationships and mutual influences among the Research variables.